2001
DOI: 10.1046/j.1468-2982.2001.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Rizatriptan Efficacy in Randomized Controlled Clinical Trials

Abstract: Data from seven randomized, placebo-controlled, double-blind phase III clinical trials were analysed to further evaluate the efficacy of rizatriptan 10 mg (n = 2068) in comparison with placebo (n = 1260) and rizatriptan 5 mg (n = 1486) for the acute treatment of a migraine attack. Migraine was diagnosed according to International Headache Society criteria. Headache severity, associated migraine symptoms and functional disability were measured immediately before dosing and at 0.5, 1, 1.5 and 2 h. Headache recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 19 publications
6
69
1
3
Order By: Relevance
“…49 Ferrari et al conducted a meta-analysis of seven randomised, placebocontrolled, double-blind phase III trials of rizatriptan (10 mg, n=2,068 or 5 mg, n=1,486) versus placebo (n=1,260) for treating an acute migraine attack. 50 Rizatriptan (10 mg) was significantly better compared with placebo for pain relief at 2 hours (71 versus 38%, p<0.001) and for the elimination of pain, nausea, photophobia, phonophobia and functional disability. In addition, more patients treated with rizatriptan than placebo had sustained pain relief over 24 hours (37 versus 18% respectively, p<0.001).…”
Section: Rizatriptanmentioning
confidence: 91%
See 1 more Smart Citation
“…49 Ferrari et al conducted a meta-analysis of seven randomised, placebocontrolled, double-blind phase III trials of rizatriptan (10 mg, n=2,068 or 5 mg, n=1,486) versus placebo (n=1,260) for treating an acute migraine attack. 50 Rizatriptan (10 mg) was significantly better compared with placebo for pain relief at 2 hours (71 versus 38%, p<0.001) and for the elimination of pain, nausea, photophobia, phonophobia and functional disability. In addition, more patients treated with rizatriptan than placebo had sustained pain relief over 24 hours (37 versus 18% respectively, p<0.001).…”
Section: Rizatriptanmentioning
confidence: 91%
“…Except for the elimination of nausea, the 10 mg dose was significantly more effective than 5 mg on all endpoints at 2 hours and maintained over 24 hours (38 versus 32% for rizatriptan 10 mg and 5 mg, respectively, p=0.001). 50 Rizatriptan (5 mg for body weight 20-39 kg, 10 mg >40 kg) has also been evaluated in 96 young patients aged 6-17 years in a double-blind, placebo-controlled, cross-over trial. 51 Patients receiving either dose of rizatriptan achieved headache relief by two grades at 2 hours compared with placebo (p<0.001).…”
Section: Rizatriptanmentioning
confidence: 99%
“…In terms of sustained headache response, defined as relief of headache pain within 2 hours, and no recurrence or use of rescue medication within 24 hours, eletriptan appears to offer a clear advantage over all the other triptans, with the 80-mg dose showing a sustained response rate of 57%, while rizatriptan offers the highest sustained pain-free response, in the range of 25% [13]. Sustained headache response and sustained pain-free response results are highly correlated with restoration of normal levels of functioning, and is important from a pharmacoeconomic standpoint because it is the outcome measure that best determines the average number of pills taken per migraine attack.…”
Section: Efficacymentioning
confidence: 97%
“…A summary of the efficacy of rizatriptan on these measures in a pooled analysis of the phase 3 trials plus other randomized controlled trials performed up to 1998 is shown in Table 2. 58 The trials also demonstrated that rizatriptan had a fast onset of action with benefits over placebo being seen from 30 minutes in some cases. In addition to looking at effects on migraine symptoms, the trials also assessed patient satisfaction with medication at 2 hours.…”
Section: S6mentioning
confidence: 98%
“…58 Clinical adverse experiences were typically mild and short-lasting (2-3 hours). The tolerability profile of rizatriptan 10 mg in the longterm extensions was similar to that observed in the short-term studies and few patients (less than 5%) discontinued due to clinical adverse events, although the overall discontinuation rate for any reason was higher.…”
Section: S6mentioning
confidence: 99%